Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1177/014556130007900712
|View full text |Cite
|
Sign up to set email alerts
|

Fascioperiosteal Flap and Neo-Osteogenesis in Radical Mastoidectomy: Long-Term Results

Abstract: We performed an analysis oflong-term out com es data on 60 patients with chronic otitis media with cholesteatoma who had und ergone a surgical procedure bas ed on an improved radical mastoidectomy and an inferiorly based fas cioperiostealflap. Wefound that at the 2-, 7-, 10-, and 13-year postoperative followup visits, all mastoid cavities were healthy and redu ced in volum e. At the f inal examination, the mean cavity volume was found to be decr eased by 39% ofthe mean volume measured 1 month postoperatively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The results of the studies, reported by Kahramanyol et al [8] in which mastoid cavities were obliterated with fascioperiosteal flap, have shown that the mastoid cavity volume was decreased by 39% due to neo-osteogenesis under fascioperiosteal flap, and that the obliteration has stayed in long term has shown radiologically [9]. In our study it has shown a nearly twofold increase in EAC volume and no significant difference after 24th months.…”
Section: Discussionsupporting
confidence: 61%
“…The results of the studies, reported by Kahramanyol et al [8] in which mastoid cavities were obliterated with fascioperiosteal flap, have shown that the mastoid cavity volume was decreased by 39% due to neo-osteogenesis under fascioperiosteal flap, and that the obliteration has stayed in long term has shown radiologically [9]. In our study it has shown a nearly twofold increase in EAC volume and no significant difference after 24th months.…”
Section: Discussionsupporting
confidence: 61%
“…Nine articles that were not available in English were also excluded. Forty‐three articles were used in the quantitative analysis 1‐9,15‐48 . Figure 1 shows our PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…The acoustic properties of an obliterated cavity are considered to be better than an open cavity [ 18 - 21 ]. It is possible that new bone formation facilitated by a periosteal flap in the CWD cavity may provide acoustic properties similar to those of the normal ear canal [ 18 , 22 , 23 ]. Our results with hearing were acceptable, showing that in CWD surgery, the tympanoplasty does save the hearing even in the long run.…”
Section: Discussionmentioning
confidence: 99%